Centrifugally spun silica (SiO2) nanofibers for high-temperature air filtration - POLAT, YUSUF (TAYLOR & FRANCIS INC, 2019)
In this study, silica-based nanofibers were produced via centrifugal spinning (C-spin) and subsequent calcination. The produced heat resistant media was challenged with NaCl nanoparticles to investigate their filtration performance. To obtain inorganic SiO2 nanofibers, C-spun organic PVP-TEOS nanofibers were calcinated at 300-600 degrees C. Effects of solution concentration and calcination temperature on crystallinity, morphology and air filtration performance of nanofibers were investigated. Scanning electron microscopy (SEM) analysis was performed to analyze fiber diameter and morphology of nanofibrous webs. Differential thermal analysis (DTA) was realized for the thermal behavior of samples. Moreover, X-ray diffraction (XRD) and Fourier transform infrared spectra (FTIR) analysis were realized for further characterization. In addition to the chemical and morphological analysis, the ductility of the samples was investigated via tensile tests. Finally, calcinated webs were challenged with 0.4 mu m salt particles to analyze their filtration performance. The calcinated 5 wt% TEOS/PVP silica nanofiber webs were more brittle due to three times lower precursor content. Therefore, flexibility (percent elongation) of 15 wt%TEOS/PVP sample was nearly five times higher than 5 wt%TEOS/PVP sample. The calcinated 15 wt%TEOS/PVP sample showed the highest filtration performance among all the silica nanofibers. The average fiber diameter of the optimized web was found to be the lowest, which is around 521 +/- 308 nm, which resulted in enhanced filtration efficiency around 75.89%. Copyright (c) 2019 American Association for Aerosol Research
Keywords: Jing Wang; FABRICATION; PERFORMANCE; NANOTUBES; MEMBRANES; POLLUTION